Respons Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Pemberian Kompos TKKS dan Jarak Tanam di Dataran Rendah - Tombang Romario Simangunsong; Jonatan Ginting; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2016)
This research was to study the response of the growth and yield of shallot (Allium ascalonicum L.) on the aplication of palm oil empty fruit bunches compost and the plant spacing in the lowlands. This research was conducted at the land of citizens in Jl. Pasar I No. 89, Tanjung Sari Village, District of Medan Selayang from May until July 2015, This research used Split Plot Design, as a main plot was the plantspacing (20 cm x 20 cm, 20 cm x 15 cm and 20 cm x 10 cm), as a Sub plot was palm oil empty fruit bunches compost (0 kg, 0.5 kg, 1 kg, 1.5 kg and 2 kg). The results showed that the giving of palm oil empty fruit bunches compost was significantly affected to the fresh weight per sample,the dry weight per sample, fresh weight per plot and dry weight per plot where the best on to gave 1.899 kg/plot could increased the fresh weight per plot was 232 g. Best treatment on fresh weight bulb per plot was J1 with giving 1.87 kg/plot i,e, 234.86 g and dry weight bulb per plot on J3 with giving 1.899 kg/plot i,e, 230 g.Keywords: shallot, plant spacing, palm oil empty fruit bunches compost.This research was to study the response of the growth and yield of shallot (Allium ascalonicum L.) on the aplication of palm oil empty fruit bunches compost and the plant spacing in the lowlands. This research was conducted at the land of citizens in Jl. Pasar I No. 89, Tanjung Sari Village, District of Medan Selayang from May until July 2015, This research used Split Plot Design, as a main plot was the plantspacing (20 cm x 20 cm, 20 cm x 15 cm and 20 cm x 10 cm), as a Sub plot was palm oil empty fruit bunches compost (0 kg, 0.5 kg, 1 kg, 1.5 kg and 2 kg). The results showed that the giving of palm oil empty fruit bunches compost was significantly affected to the fresh weight per sample,the dry weight per sample, fresh weight per plot and dry weight per plot where the best on to gave 1.899 kg/plot could increased the fresh weight per plot was 232 g. Best treatment on fresh weight bulb per plot was J1 with giving 1.87 kg/plot i,e, 234.86 g and dry weight bulb per plot on J3 with giving 1.899 kg/plot i,e, 230 g.Keywords: shallot, plant spacing, palm oil empty fruit bunches compost.